2001
DOI: 10.1002/chin.200105061
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Surface‐Mediated Reactions. Part 9. Selective Oxidation of Primary and Secondary Amines to Hydroxylamines.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…28 However, we found hydroxylamine 9 was very susceptible to further oxidation with mCPBA. 29 As evidenced by many side product spots on the TLC plate and M -1, M, and M + 1 peaks in the mass spectrum, we concluded that the mCPBA oxidation reaction was complicated by overoxidation. Varying the mCPBA ratio and the reaction temperature did not help circumvent the problem.…”
Section: Chemistrymentioning
confidence: 77%
“…28 However, we found hydroxylamine 9 was very susceptible to further oxidation with mCPBA. 29 As evidenced by many side product spots on the TLC plate and M -1, M, and M + 1 peaks in the mass spectrum, we concluded that the mCPBA oxidation reaction was complicated by overoxidation. Varying the mCPBA ratio and the reaction temperature did not help circumvent the problem.…”
Section: Chemistrymentioning
confidence: 77%
“…8 The latter is finally dehydrated to form an imine. 8,9 These changes not only alter the structural and physicochemical properties of the membrane but also cause chlorination degradation of the PA selective layer, eventually leading to the loss of membrane selectivity in separation. 8,10 Therefore, exploring novel PA membranes with excellent chlorine resistance has become a research focus recently.…”
Section: Introductionmentioning
confidence: 99%